Rice Husk Biochar as an Amendment to Improve Sweet Corn Performance on Bengkulu Entisols - Welly Herman; Umi Salamah; Erlina Rahmayuni; Zulkarnain Zulkarnain (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: Entisol soil in the coastal area of ​​Bengkulu has low fertility with limited organic matter and nutrient contents, so it requires soil amendments to increase plant productivity. Aim: This study aims to evaluate the effectiveness of rice husk biochar on improving soil chemical properties and increasing sweet corn (Zea mays saccharata) yield. Methods: The experiment was conducted on a polybag scale (10 kg of soil per polybag) using a Completely Randomised Design (CRD) with four doses of rice husk biochar (0, 5, 10, and 15 t/ha), with each treatment repeated six times. Biochar was produced through indirect pyrolysis at a temperature of approximately 400 °C, incubated for four weeks, and applied to the soil at 50% of the recommended fertilizer dose. Results: The analysis results showed that the application of rice husk biochar had a significant effect (p < 0.05) on increasing soil pH, organic carbon (C), total nitrogen (N), and cation exchange capacity (CEC). A dose of 10 t/ha increased soil pH from 6.01 to 6.61, organic C from 2.09% to 2.81%, total N from 0.11% to 0.17%, and CEC from 4.98 to 5.64 cmol(+)/kg, significantly higher than the control (p < 0.05). This increase in fertility directly impacted the growth and yield of sweet corn, with cob weight reaching 437.5 g, significantly greater than the control at p < 0.05, but not significantly different from the dose of 15 t/ha. Conclusion: Thus, rice husk biochar at a dose of 10 t/ha effectively improves Entisol soil quality and increases sweet corn yields, and has the potential to be applied as a sustainable agricultural innovation in tropical marginal lands.